Moderate-Severe Endometriosis Shows Higher CA-125 Serum Level Compared to Minimal-Mild Endometriosis - Jhonny Yudho (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To investigate and compare serum profile of CA-125, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in various stages of endometriosis. Methods: Forty endometriosis patients’ blood samples were taken prior to laparoscopic surgery for various indications. Diagnosis of endometriosis was confirmed by laparoscopy. Independent T test methods were used for statistical analysis. ROC analysis was examined for each variable. Results: The mean level of CA-125 serum was 12.0 vs. 36.3 U/ml (p < 0.05); ESR serum was 11 vs. 12.8 mm/hour (p > 0.05); CRP serum was 0.7 vs. 0.3 (p > 0.05) for endometriosis stage I-II and stage III-IV, respectively. The optimal cut off point to discriminate endometriosis stage I-II and III-IV was 16.9 U/ml with sensitivity 83% and specificity 81%. Conclusion: The CA-125 serum level was increased for moderatesevere compare to minimal mild endometriosis patient. [Indones J Obstet Gynecol 2012; 36-3: 121-4] Keyword: CA-125, CRP, endometriosis, ESR, serum